Cyber behavior : concepts, methodologies, tools, and applications - IGI eBooks; IGI Global; Information Resources Management Association (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2014)
"This book explores the role of cyberspace in modern communication and interaction, including considerations of ethics, crime, security, and education, with chapters on a variety of topics and concerns inherent to a contemporary networked society"--Provided by publisher.
Fundamental concepts and theories -- Development and design methodologies -- Tools and technologies -- Utilization and application -- Organizational and social implications -- Managerial impact -- Critical issues -- Emerging trends.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 06/19/2014).
Keywords: Internet users -- Psychology; Internet -- Psychological aspects; Information technology -- Psychological aspects; Cyber behavior; Cyber crime; Data mining; Ethics; Internet education; Online interaction; Security; Virtual environments; Web 2.0; Electronic books